2008
DOI: 10.2174/138920008786927785
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evidence of Herb-Drug Interactions: A Systematic Review by the Natural Standard Research Collaboration

Abstract: As herbal products (and dietary supplements in general) continue to grow in popularity, patients and health care providers should be vigilant of potential herb-drug interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
92
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(96 citation statements)
references
References 0 publications
0
92
0
4
Order By: Relevance
“…Наибольшее влияние на метаболизм антикоагулянтов и антиагрегантов ока-зывают зверобой, чеснок, имбирь, гинкго, грейпфрут, женьшень. Эксперты считают, что прием этих трав должен быть прекращен за 2 недели перед оператив-ным лечением [8,9]. При одновременном приеме ЛП гинкго, чеснока с варфарином или с аспирином/кло-пидогрелем возможно избыточное повышение кон-центраций ЛП в крови и возникновение кровотече-ний.…”
Section: The Influence Of Lifestyle On the Efficacy And Safety Of Medunclassified
“…Наибольшее влияние на метаболизм антикоагулянтов и антиагрегантов ока-зывают зверобой, чеснок, имбирь, гинкго, грейпфрут, женьшень. Эксперты считают, что прием этих трав должен быть прекращен за 2 недели перед оператив-ным лечением [8,9]. При одновременном приеме ЛП гинкго, чеснока с варфарином или с аспирином/кло-пидогрелем возможно избыточное повышение кон-центраций ЛП в крови и возникновение кровотече-ний.…”
Section: The Influence Of Lifestyle On the Efficacy And Safety Of Medunclassified
“…For instance, the pharmacokinetic interactions between St. John's wort and certain prescribed drugs (16) or between cat's claw and specific blood medication (17) are well-documented. Several research papers review the interaction between herbs, homeopathic and allopathic drugs (18)(19)(20)(21). The interactions between traditional Chinese medicines and western therapeutics have been reviewed recently (22).…”
Section: Implications For Policy Makersmentioning
confidence: 99%
“…Ulbricht et al 58 identified more than 80 herbs or herbal products (including plants, fungi, algae, and common constituents) showing clinical interactions with prescription and OTC drugs. Drugs with anticoagulant/antiplatelet activity (e.g.…”
Section: Toxicitymentioning
confidence: 99%